ORAL LITERATURE OF BAJO TRIBE IN SOUTH HALMAHERA: A DOCUMENTATION OF ORAL LITERATURE AS A REFLECTION OF LOCAL WISDOM - Magfirah, Sulmi; Irsyadi, Hudan; Talaohu, Ahmad Rifani (Lire Journal (Journal of Linguistics and Literature), 2025)
The study objective is to describe and analyse the meaning of oral literature of the Bajo tribe and to document oral literature as a reflection of local wisdom for the Bajo tribe. The method used in this research is a qualitative descriptive, which analyses the text one by one according to its meaning using thematic analysis approach. The data processing includes transcribed and documented texts in oral literature found in the Bajo Tribe of South Halmahera, including the original and translation texts. The findings reveal that the Legend of Batu Tolu and Batu Anyur, and the Legend of the Rich People Island are oral literature from the Bajo Tribe in South Halmahera, containing key themes such as: praise for Ternate and Tidore Royal families; hopes and prayers; respect for others; and understanding the ancestral heritage culture to uphold togetherness for the next generation. This study carries significant societal implications, particularly in preserving cultural heritage and strengthening community identity. Ultimately, by documenting and analyzing the oral traditions of the Bajo people, this research highlights the crucial role of storytelling in transmitting local wisdom, moral values, and environmental knowledge across generations.